Subsurface strata failure and movement based for improving gas emission control: Model development and application. Issue 9 (25th May 2020) - Cheng, Jianwei; Wang, Zui; Li, Siyuan; Song, Wanting; Lu, Weidong; Zhang, Yongjun; Zhao, Kang
Abstract: In underground mining operations, the overlying strata move, deform, and crack as the underground working face advances due to strata breakage, failure, and subsidence, forming a "vertical three zone" over the mined out area. The permeability of strata under mining changes differently in different zones. Therefore, studying the distribution of strata permeability is very important to obtain knowledge of gas migration pattern in the overlying strata in order to increase the gas extraction efficiency. In this study, a series of numerical models are developed to describe the overlying strata movement for three different zones. In detail, models for calculating the strata subsidence for fracture and bending zones and analyzing strata collapsing development for the caving zone are proposed based on the influence function method and mechanical analyses. In addition, on the basis of such models, a new comprehensive model to describe the strain‐porosity‐permeability of strata is developed. In the case study of applying such models in an underground mine, the reliability of the strata movement model is verified and the permeability change is also calculated, which gives a good guidance to design the location of gas drainage roadway practices in the future. The field engineering practice shows its good application. Abstract : A series of numerical models are developed to describe the overlying strata movement in three different zones. In detail, models for calculating the strata subsidence for fracture and bending zones and analyzing strata collapsing development for the caving zone are proposed based on the influence function method and mechanical analyses. In addition, on the basis of such models, a new comprehensive model to describe the strain‐porosity‐permeability of strata is developed. In the case study of applying such models in an underground mine, the reliability of the strata movement model is verified and the permeability change is also calculated.